2018
DOI: 10.1186/s13104-018-3295-8
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of institutional delivery service and associated factors among mothers in North West Ethiopian

Abstract: ObjectiveThe aim of this study was to assess institutional delivery and its associated factors in Benishangul-Gumez region, North-West of Ethiopia. The data were obtained at community level in a single survey within 1 month and there is no continuation of this study or previously published part elsewhere.ResultsAmong the 428 eligible respondents recruited for this study, 427 of them responded completely to the interview, giving a response rate of 99.8%. Of the total (427) respondents, 51.1% women delivered the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
49
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 13 publications
14
49
2
Order By: Relevance
“…Finally, 43 studies were screened for full-text review and 24 were included to the prevalence and/ or associated factors analysis ( Figure 2). Seven (7) Studies were found in Amhara region [22,23] [ [24][25][26][27][28], Nine (9) in Oromia [29][30][31][32][33][34][35][36][37], two in Afar [38,39], one in Bienishangul-Gumuz [40] ,three(3) in Southern Nation Nationalities and Peoples region (SNNPR) [41][42][43],one in Gambiela [44] and one in Tigray&Oromiya [45].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Finally, 43 studies were screened for full-text review and 24 were included to the prevalence and/ or associated factors analysis ( Figure 2). Seven (7) Studies were found in Amhara region [22,23] [ [24][25][26][27][28], Nine (9) in Oromia [29][30][31][32][33][34][35][36][37], two in Afar [38,39], one in Bienishangul-Gumuz [40] ,three(3) in Southern Nation Nationalities and Peoples region (SNNPR) [41][42][43],one in Gambiela [44] and one in Tigray&Oromiya [45].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Finally, 43 studies were screened for full-text review and 24 were included to the prevalence and/ or associated factors analysis (Figure 2). Seven (7) Studies were found in Amhara region [23,24] [25][26][27][28][29], Nine (9) in Oromia [30][31][32][33][34][35][36][37][38], two in Afar [39,40], one in Bienishangul-Gumuz [41] ,three(3) in Southern Nation Nationalities and Peoples region (SNNPR) [42][43][44],one in Gambiela [45] and one in Tigray&Oromiya [46].…”
Section: Study Characteristics and Study Participantsmentioning
confidence: 99%
“…The pooled effect of four studies [27,28,33,41] showed that women who had their first pregnancy between the age of 15-24 years were 3.60 times as likely to give birth in health institution than those who became pregnant after 35 years of age (AOR= 3.59; 95% CI 2. 27 5.69 ).…”
Section: Maternal Age At First Pregnancymentioning
confidence: 99%
See 2 more Smart Citations